The Effectiveness of Smart Box Media on The Knowledge and Attitude of MI Hidayatus Syam Students on PHBS at School Healthy Snack Indicators - Anabela, Aisha; Sari, Puspita; Rifqi Azhary, Muhammad; Ridwan, M.; Herwansyah, Herwansyah; Reskiaddin, La Ode (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Health is an important problem in Indonesia, especially the health problem of school-aged children. Based on 2023 Jambi Health Service data, West Tanjung Jabung Regency implemented the lowest level of health promotion in schools.  Students' lack of knowledge in PHBS indicators of healthy snacks can cause various health problems. For this reason, interesting media innovations such as Smart Box are needed as a health promotion tool for school-aged children. Objective: This research aims to determine the influence of Smart Box Media on students' knowledge and attitudes regarding PHBS indicators of healthy snacks. Method: The design of this research is a quasi-experiment with a one group pretest and posttest research design. This research was conducted in December 2024. Result and Discussion: The results show that the average student knowledge score increased from the pretest 54.00 to 73.00. The attitude score increased from 58.50 to 75.08 on the posttest. Conclusions: There is an influence of Smart Box PHBS healthy snacks on increasing the knowledge and attitudes of MI Hidayatus Syam students with a p-value of 0.001